Aktivitas Antibakteri Ekstrak Etanolik Daun Singkil (Premna corymbosa) Terhadap Bakteri Salmonella typhi Secara In Vitro - Margareta Retno Priamsari; Eka Aprilia Nuraida (Unit Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Bhakti Mulial, 2022)
Singkil leaves (Premna corymbosa) contain secondary metabolites in the form of flavonoids, saponins, tannins and triterpenoids/steroids that can inhibit the growth of Salmonella typhi bacteria. The purpose of this study was to determine the antibacterial activity of the ethanolic extract of singkil leaves in inhibiting Salmonella typhi bacteria in vitro. Extraction was carried out using maceration method with 70% ethanol solvent, then continued with extract quality control and phytochemical screening of flavonoid compounds, saponins, and tannins. Antibacterial activity using disc diffusion method with Mueller Hilton Agar (MHA) media. The antibacterial concentration of the extract was 50%, 60%, 70%, 80%, and 90%; positive control (chloramphenicol 30µg) and negative control (DMSO 10%) with 3 replications. Incubation was carried out at 37°C for 24 hours. The parameter observed was a clear zone formed around the paper disc. The data obtained were then analyzed statistically using Kruskal Wallis followed by Man Whitney with a 95% confidence level. The results showed that variations in the concentration of the ethanolic extract of singkil leaves had a significant effect (p<0.15). The largest inhibition zone was seen at a concentration of 90% at 20.1 ± 1.05 mm with a very strong category. The minimum inhibitory power produced at a concentration of 70% was 17.7 ± 0.88 mm with a strong inhibition category.